Pelatihan “Sex? It Isn’t Taboo Anymore” untuk Meningkatkan Pengetahuan dan Asertivitas Seksual Remaja - Ellyana Dwi Farisandy; Endang Retno Surjaningrum (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
This study aims to determine the effect of sexuality training to increasing the knowledge of sexuality and sexual assertiveness behavior in adolescents. This study used preexperimental design, with one group pretest posttest design, where only one group will be given treatment. The research sample was selected using total sampling method. The subjects of this study were 12 members of Posyandu Puskesmas X aged 11-20 years. Sexuality knowledge was measured using an instrument prepared by researchers, while Sexual Assertiveness Scale (SAS) was used to measure sexual assertiveness. The intervention consists of eight sessions of sexuality training for two days. Data was analyzed using wilcoxon signed rank test. The results show that sexuality training is effective to increasing knowledge and sexual assertiveness, and it is expected to be able to prevent teenagers from engaging in premarital sexual behavior.